Iron and Folic Acid Supplementation Compliance and Associated Factors among Pregnant Women Attending Antenatal Clinic in Shalla District, Southwest Ethiopia: A Cross-Sectional Study - Aman Kedir Obsa; Yadesse Tegene; Achamyelesh Gebretsadik (Journal of Nutrition and Metabolism)
Background. Iron-folate supplementation for a pregnant mother is a cost-effective intervention to reduce iron deficiency anemia during pregnancy. The aim of this study was to assess the iron-folic acid supplements and associated factors among pregnant women attending antenatal clinics in the public health center of Shalla district, Southwest Ethiopia. Methods. Institutional-based cross-sectional study design was conducted among 402 randomly selected pregnant mothers between February and April 2019. Data were collected using an interviewer-administered structured questionnaire from pregnant mothers attending antenatal care and using iron-folate supplements. Descriptive and multivariate logistic regression analyses were employed. Results. Pill count compliance rate was found to be (154) 38.3%. Pregnant mothers who had anemia in their previous pregnancy [(AOR = 11.35, 95% CI: 4.76–27.03)], counseling on iron-folate supplements [(AOR = 11.39, 95% CI: 5.09–27.03)], awareness of the benefit of the iron-folate supplements [(AOR = 2.22, 95% CI: 1.18–3.92)], and being a member of the Health Development Army [(AOR = 2.11, 95% CI: (1.2, 3.9)] were significantly associated with compliance with iron-folate supplement. Conclusion. Compared to the World Health Organization cut-off point, the pill count compliance rate of iron-folate supplementation among pregnant women in the study area was very low. Previous history of anemia and lack of knowledge about its benefit were some of the factors associated with it. Therefore, the healthcare providers should give continuous awareness creation and counseling services focusing on the benefit of iron-folate supplementation for pregnant mothers and their neonates.